FORMATION OF ANALYTICAL THINKING IN FUTURE TEACHERS OF PHILOLOGY (USING THE EXAMPLE OF ANALYZING RUSSIAN LANGUAGE TEXTBOOKS FOR INCOMPLETE SENTENCES) (CAHIERS MAGELLANES-NS, 2024)
Modern society requires an analytically thinking teacher who is able to instill analytical skills in his/her students; therefore, when preparing future teachers, in particular teachers of Russian literature, it is important to develop their analytical thinking. One of the ways of its formation can be the ability to work with didactic material, to choose the best textbooks for teaching certain lexical and grammatical topics.